Population-based Cardiovascular Disease Prevention Measures Aimed at Reducing Salt Intake: Analysis of International Strategies and Prospects for Implementation in the Russian Federation - Yu. A. Balanova; A. V. Kontsevaya; N. S. Karamnova; D. K. Mukaneeva; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
High salt intake is an important risk factor for cardiovascular diseases (CVD), closely related to the level of blood pressure in the population. The purpose of the review: to study population-based interventions for CVD prevention, aimed at reducing salt intake; to assess the potential for their implementation in the Russian Federation. We presented population-based strategies for dietary salt intake reduction used in different countries. The main components of strategies aimed to correct this risk factor in the Russian Federation were identified. The main components of the population-based approach to reducing salt intake are: determining population salt consumption, identifying sources of salt in the diet, monitoring of salt content in products, engaging with the food industry, consumer awareness campaigns, changes in product labeling, tax measures. An integrated approach to the problem is the most successful. Measures which were highly effective have not yet been fully implemented in the Russian Federation. At the moment, taxation of high-salt foods and tax subsidies for healthy food are not applied. Food manufacturers are not sufficiently involved - there are no legislatively introduced measures to reduce salt through food reformulation. Firstly it has to be applied to diet-forming products that are consumed daily, such as bakery and dairy products, and meat products.